Distribution of Regulatory T-Cell (Cd4+, Cd25+) in the Peritoneal Fluid of Endometriosis Patients - Rusdi, Gazali (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objectives: To observe the distribution of Regulatory T-cell (CD4+, CD25+) in the peritoneal fluid of endometriosis patients, as related to the local immune system of the peritoneum. Method: A cross-sectional descriptive research Perioneal fluid was taken from endometriosis patients and non-endometriosis patients who underwent laparoscopic or laparotomy surgery at Raden Saleh Reproductive Health Clinic and Central Operating Theatre between June 2008 to March 2009. Total leukocyte and its differential count was counted manually. Regulatory T-cell was labelled with monoclonal antibodies for CD45 (PerCP-347464), CD4 (SIPC- 340133) dan CD25 (PE-341009) and counted by Flowcytometry (Facscalibur) using cellquest pro software. Data were collected and analyzed with SPSS ver 11 software. Result: Thirty-three patients were participated in this study, 12 non-endometriosis and 21 endometriosis patients were analyzed. 10 endometriosis patients were classified as minimal-mild, while 11 others were in moderate-severe stage. Higher median level of Regulatory T-cells were found in endometriosis patients (0.52%) compared to non-endometriosis cases (0.12%), even it was not significantly different (p 0.403). The median level of Regulatory T-cell in minimal-mild endometriosis (0.46%) was not significantly different with moderate severe endometriosis (0.52%) (p 0.981). Conclusion: The percentage and total number of Regulatory Tcell in the peritoneal fluid did not show significant difference between endometriosis and non-endometriosis patients. Endometriosis patients shows tendency of higher percentage and total number of Regulatory T-cell than non-endometriosis group. The stage of endometriosis apparently does not show any significant difference in terms of Regulatory T-cell in peritoneal fluid. [Indones J Obstet Gynecol 2010; 34-1:19-23] Keywords: Regulatory T-cells, CD4 CD 25, peritoneal fluid, endometriosis